2017
DOI: 10.5606/tgkdc.dergisi.2017.13843
|View full text |Cite
|
Sign up to set email alerts
|

The Levitronix CentriMag ventricular assist device as a bridge to decision in patients with end-stage heart failure: Our single-center experience

Abstract: Rabuş MB, Salihi S, Hasanov S, Fedakar A, Çevirme D, Balkanay M. The Levitronix CentriMag ventricular assist device as a bridge to decision in patients with end-stage heart failure: Our single-center experience. Turk Gogus Kalp Dama 2017;25(4):543-9. ABSTRACTBackground: In this study, we report early outcomes of Levitronix CentriMag device implantation for bridge to decision for patients with end-stage heart failure in a single center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Borisenko [1] reviewed 53 studies about VAD mean duration, survival rate, and complication rate, reported that the mean support day was 8 days, survival rate while on support was 62-83%, and the 30-day survival was 41-82.2%, depending on the placement indication. Furthermore, thrombosis and neurological complication rate was 7%, and device failure was observed in 0.08% of patients [5]. Therefore, patients without neurological deficit should quickly be bridged to either heart transplantation or implantation of a permanent VAD if cardiac grafts are unavailable [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Borisenko [1] reviewed 53 studies about VAD mean duration, survival rate, and complication rate, reported that the mean support day was 8 days, survival rate while on support was 62-83%, and the 30-day survival was 41-82.2%, depending on the placement indication. Furthermore, thrombosis and neurological complication rate was 7%, and device failure was observed in 0.08% of patients [5]. Therefore, patients without neurological deficit should quickly be bridged to either heart transplantation or implantation of a permanent VAD if cardiac grafts are unavailable [5].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, thrombosis and neurological complication rate was 7%, and device failure was observed in 0.08% of patients [5]. Therefore, patients without neurological deficit should quickly be bridged to either heart transplantation or implantation of a permanent VAD if cardiac grafts are unavailable [5]. Currently, the CentriMag system could be used as a bridge therapy to decision, particularly when patients undergo CPR or when the consciousness level is unclear, which is contraindicated for transplantation [6].…”
Section: Discussionmentioning
confidence: 99%